Can Backward-looking and Forward-looking Information Debias Prospect Effect in Earnings Announcement? - Jogianto Hartono; Sri Wahyuni (Gadjah Mada International Journal of Business, 2017)
This study examines the important issue of whether additional pieces of information about the earnings’ characteristics (their quantitative description and predicted earnings) can debias the prospect effect of the earnings’ announcement. The prospect effect bias can be mitigated by the availability of clear information and an integrated disclosure. Additional information that is included with the previous information will make the investors’ beliefs stronger  and it will debias any psychological effects.This research confirms the prospect effect’s bias that investors react more negatively when evaluating a company’s performance after a negative earnings information disclosure rather than react positively in evaluating the performance for a positive earnings information disclosure. The results also show that when additional pieces of information, such as a quantitative description and predicted earnings are added, they can mitigate the prospect effect’s bias. Additional information of predicted earnings as forward-looking oriented information has a stronger debiasing effect than that of additional information of a quantitative description as backward-looking oriented information.